Comparison of Intestinal Response of Chicks from Light and Heavy Eggs to Posthatch Fasting - Riccardi, Rafael Raile; Malheiros, Euclides Braga; Boleli , Isabel Cristina (International Journal of Poultry Science, 2010)
The effects of posthatch fasting on villi height and number, crypt depth and number of globet cells in duodenum, jejunum and ileum of broiler chicks from heavy and light eggs were compared. The 2 x 3 x 3 factorial design (egg weight: light and heavy eggs; treatments: with water and feed, with water, without water and feed; treatment duration: 24, 48 and 72 h) was used. The villi presented higher size in chicks from heavy than from light eggs. The fasting resulted in lower villi in duodenum (at 48 h), jejunum and ileum (at 72 h). The villi number increased in duodenum and jejunum of chicks from light eggs and only in jejunum of chicks from heavy eggs, but the increase was more accented in chicks from light ones. The fasting reduced the globet cells number in jejunum. Water intake avoided the fasting effects on villi height but had no effect on villi number. Chicks from heavy eggs fed with water and ration presented deeper crypts in all regions of the small intestine. The duodenum and ileum crypt depth of the chicks from heavy eggs reduced when they were submitted to fasting and when they were fed only with water. The results showed that chicks from light eggs were more affected than chicks from heavy eggs. The water intake partially avoided the fasting effects.